2005
DOI: 10.1124/mol.104.009878
|View full text |Cite
|
Sign up to set email alerts
|

GABAAReceptor-Associated Protein Regulates GABAAReceptor Cell-Surface Number inXenopus laevisOocytes

Abstract: GABA A receptor-associated protein (GABARAP) was isolated previously in a yeast two-hybrid screen using the intracellular loop of the ␥2 subunit of the GABA A receptor as bait. GABARAP has been shown to participate in the membraneclustering and intracellular-trafficking of GABA A receptors, including a stimulation of the surface expression of GABA A receptors. To assess this quantitatively, we used Xenopus laevis oocytes expressing ␣1␤2␥2S-containing GABA A receptors to demonstrate that coexpression of GABARAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 28 publications
2
49
0
Order By: Relevance
“…NSF has been implicated in the exocytosis of many receptor types in the CNS, including GABA A Rs, AMPARs, ␤2-adrenergic receptors, and dopaminergic receptors (for review, see Zhao et al, 2007), so perhaps the specificity of NSF-mediated receptor delivery is conferred by associated proteins such as GABARAP. Several studies have shown that exogenous GABARAP can lead to increased surface GABA A R expression (Leil et al, 2004;Chen et al, 2005), but our data provide the first indication of a similar role for the endogenous protein. These results at first seem at odds with data from a GABARAP knock-out mouse that showed no alteration in GABA A R expression (O'Sullivan et al, 2005).…”
Section: Discussionsupporting
confidence: 53%
“…NSF has been implicated in the exocytosis of many receptor types in the CNS, including GABA A Rs, AMPARs, ␤2-adrenergic receptors, and dopaminergic receptors (for review, see Zhao et al, 2007), so perhaps the specificity of NSF-mediated receptor delivery is conferred by associated proteins such as GABARAP. Several studies have shown that exogenous GABARAP can lead to increased surface GABA A R expression (Leil et al, 2004;Chen et al, 2005), but our data provide the first indication of a similar role for the endogenous protein. These results at first seem at odds with data from a GABARAP knock-out mouse that showed no alteration in GABA A R expression (O'Sullivan et al, 2005).…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, the single channel conductance was significantly higher in L929 cells coexpressing ␣1␤2␥2S subunits with GABARAP than without (Everitt et al, 2004), showing high conductance states similar to those observed in native receptors (Fatima-Shad and Barry, 1992;Curmi et al, 1993;Birnir et al, 1994Birnir et al, , 2001. Recently, we and others reported that overexpression of GABARAP increased the cell-surface number of GABA A receptors (Leil et al, 2004;Boileau et al, 2005;Chen et al, 2005). Immunostaining microscopy showed that GABARAP colocalized with intracellular vesicular GABA A receptors and to some extent with plasma membrane GABA A receptors but not with synaptically localized GABA A receptors and gephyrin (Kneussel et al, 2000;Kittler et al, 2001;Leil et al, 2004).…”
Section: Introductionmentioning
confidence: 83%
“…Capped mRNA (cRNA) was synthesized by in vitro transcription from Apa I-linearized cDNA constructs using the mMessage Machine kit (Ambion, Austin, TX) as described previously (Chang et al, 2003;Chen et al, 2005). Oocytes were injected with a total volume of 50 nl of cRNA mixed in a ratio of 1:1:2:4 (␣1:␤2:␥2: H 2 O, GABARAP or mutant GABARAP).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, we attended to GABARAP, a linker protein between GABA A R and tubulin (Wang et al, 1999). The number and/or function of surface GABA A R can be regulated by GABARAP in both heterologous expression systems and neurons (Chen et al, 2000(Chen et al, , 2005Nymann-Andersen et al, 2002;Everitt et al, 2004;Leil et al, 2004;Luu et al, 2006). However, implication of GABARAP in synaptic plasticity has not been explored.…”
Section: Introductionmentioning
confidence: 99%